Foot Osteomyelitis in Patients Without Diabetes. Issue 4 (July 2018) - Mitbander, Urvashi; Musher, Daniel; Mindru, Cezarina; Barshes, Neal R.
Abstract : Background: Virtually all studies describing osteomyelitis of the foot have confined themselves to patients with diabetes mellitus. Although much less common, infection of bones in the feet does occur in patients without diabetes. We characterized episodes of foot osteomyelitis occurring in patients without diabetes to help guide clinical management. Methods: Patients treated for probable or definite osteomyelitis at the Michael E. DeBakey Veterans Affairs Medical Center from January 2011 to March 2015 were included in this study. We reviewed patient and infection characteristics, treatments, and outcomes. Nonparametric analyses were used for comparisons. Results: A total of 184 episodes of foot osteomyelitis met inclusion criteria: 20 in patients without diabetes and 164 in patients with diabetes. Patients without diabetes were older, thinner, had better renal function, and a stronger history of cigarette smoking ( P < 0.05 for all comparisons). There were no significant differences in the proportion of patients presenting with various local or systemic signs of infection. Most episodes were polymicrobial (61% overall) and occurred in the toes (85% overall), and the metatarsals were less commonly affected in patients without diabetes (10% vs 38%, P = 0.01). The proportion of episodes with various isolates identified did not differ significantly. The rate of treatment failure was similar in both groups, but 1-year mortality was greater among nondiabetics ( P = 0.002). Conclusions: Patients without diabetes who develop foot osteomyelitis are older and have a much poorer short-term survival, but the presentation and microbiology of foot osteomyelitis occurring in patients without diabetes are largely similar to that occurring in patients with diabetes. Abstract : Virtually all studies describing osteomyelitis of the foot have confined themselves to patients with diabetes mellitus. Although much less common, infection of bones in the feet does occur in patients without diabetes. In this single-center study, we characterized episodes of foot osteomyelitis occurring in patients without diabetes to help guide clinical management. This study suggests that presentation and microbiology of foot osteomyelitis occurring in patients without diabetes is largely similar to that occurring in patients with diabetes.